Perilaku Orang Tua dalam Pemberian Obat Malaria pada Anak - Njakatara, Umbu Nggiku; Landi, Melkisedek; Radandima, Ester (JURNAL KESEHATAN PRIMER, 2023)
Background:  Malaria is a contagious infectious disease caused by parasites from the genus Plasmodium which is transmitted through the bite of female Anopheles mosquitoes infected with the parasite. Objective: To determine the behavior of parents in giving malaria medication to children in Mbatakapidu Village. Method: Non-Random Sampling with consecutive sampling according to the researcher's needs. 30 families were determined as samples that met the inclusion criteria. The instrument used is a questionnaire. Results: data analysis shows the behavior of parents in giving malaria medication to children from 30 respondents, there were 24 partisipants (80%) had good behavior, 5 partisipants (17%) had good behavior and the least had 1 partisipant (3%) with poor behavior.